Efficient RFID Tag Placement Framework for In Building Navigation System for the Blind - Wong, Siew Mooi; Tan, Chong Eng; Nurul Huda, bt. Nik Zulkifli (IEEE, 2010)
To date, there are increasing buildings with complex design, multi-storey and with large-scaled area. The complicated building layout could lead to certain level of difficulties for the blind or the visually impaired people in path identification in an unfamiliar surrounding such as in a new shopping complex. Radio Frequency Identification (RFID) technology appeared as an effective solution to provide location-based information to the visually impaired or blind people in indoor environment.However, RFID tags placement which can provide high positional accuracy will become an issue in effective deployment of large-scaled RFID network in a large building. This can be a very time consuming process and it is too costly to estimate the required number of RFID tags manually. In addition, the vendors do not have a standard framework or guideline in determining the tag placement process optimally. Without knowing the meaning of tag placement which provides useful location information and effective detection for the visually impaired or blind person could cause inaccurately aiding them in navigation in a large-scaled building. Therefore, a framework with automatic suggestion of intelligent optimization for RFID tags placement in a large building will be proposed in order to effectively implement RFID based navigation network for the building in terms of cost effectiveness. This framework will become the guideline to create a friendly environment for visually impaired person enabling them to enjoy high mobility in any multi-storey or large building.